Western Sufism: A Study on Historical and Models of Sufism in the West - Efendi, Efendi; Gazali, Gazali; Putri, Endrika Widdia (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2022)
The emergence of studies on Islamic mysticism or Sufism in the last few centuries, which reached its peak in the 20th century, shows that Sufism has progressed well in areas outside Islam. That is evidenced by the emergence of the Muslim community in the West, which adheres to the teachings of Sufism. This article aims to explore how the development of Sufism in the West focuses on two things (1) Examine the various theories of the introduction and early studies of Sufism in the West since the 17th century AD. (2) Assess the models and styles of Sufism that developed in the West, especially in the 20th century AD. This research is qualitative research using historical and philosophical analysis approaches. The research findings are (1) Western society's study of Sufism began in the 17th century and reached its peak in the 19th/20th centuries AD. It was marked by the many activities of translating Sufism texts. (2). In the 20th century AD, there were several models or styles of Sufism that developed in the Western world, namely hybrid Sufism, perennial Sufism, and transplant Sufism.